Removal of water-soluble dyes by conjugated organic skeletons through drainflow-diffusion filtration. Issue 4 (August 2018) - Ong, Pin Jin; Tay, Siok Wei; Hong, Liang
Abstract: This study develops an alternative adsorbent constructed by conjugated organic skeletons, which further comprises polyene segments and polyaromatic hydrocarbons (PAHs) blocks. The adsorbent was prepared through the FeCl3 -mediated dehydration of poly(vinyl alcohol) (PVA). The reaction produces pseudo-polyene ( p -polyene) segments and subsequently PAHs through further condensation of some of the polyene segments. The resulting conjugated skeletons and iron oxide/chloride species experience mutual penetration to form aggregates. Thereafter, these aggregates were subjected to sulfonation to achieve the adsorbent with pendant oxygen-containing groups to assure a negatively charged surface as well as porous structures via removing iron species. The adsorbent possesses typically rectangular-channels among the aggregates and meso (<50 nm) and macro-voids (>50 nm) inside individual aggregates. The above structural features endow the adsorbent strong capability to remove cationic methylene blue (MB, 10 mg/L) or zwitterion methyl red (MR, 10 mg/L) dyes from water or even from isopropanol through adsorption and pore diffusion and deposition. The best adsorbent demonstrates the rejection rates over 95% and flux above 17 L/min m 2 through the first 3 h at a minor pressure drop. Mechanistically, the separation outcome originates from the viscous drain flow to enhance adsorption of dye molecules on the channel wall, which is followed by diffusion of the dye molecules towards meso/macro-voids inside the rod-like aggregates.